Safety and efficacy of forefoot surgery under ankle block anaesthesia. Issue 2 (May 2014) - Russell, DF; Pillai, A; Kumar, CS
Background: Ankle block as the sole anaesthetic for forefoot surgery is not used uniformly throughout the UK despite obvious advantages and widespread use internationally. Aim: Evaluation of safety and effectiveness of performing elective forefoot surgery under ankle block anaesthesia alone in a pilot cohort of patients in a Scottish unit. Methods: Data were collected from 81 consecutive forefoot procedures (71 patients) using a standardised questionnaire including incremental pain assessment (0–10; 0 no pain, 10 severe pain). Results: Seven patients reported pain during surgery; average score 0.17. Average pain scores 6, 12, 24 and 48 h following surgery were 1.5, 3.09, 2.3 and 1.9, respectively. All patients were discharged home and walking on the same day. Conclusion: Forefoot surgery under ankle block alone may be safe and effective. Anaesthesia obtained permitted routine forefoot procedures and provided lasting post-operative analgesia. Combined with intra-operative sedation, use of ankle tourniquet and same day discharge, it had very high patient acceptance and satisfaction.